Microsatellites Provide Evidence for Y Chromosome Diversity Among the Founders of the New World (1999)
ABSTRACT: Recently, Y chromosome markers have begun to be used to study Native American origins. Available data have been interpreted as indicating that the colonizers of the New World carried a single founder haplotype. However, these early studies have been based on a few, mostly complex polymorphisms of insufficient resolution to determine whether observed diversity stems from admixture or diversity among the colonizers. Because the interpretation of Y chromosomal variation in the New World depends on founding diversity, it is important to develop marker systems with finer resolution. Here we evaluate the hypothesis of a single-founder Y haplotype for Amerinds by using 11 Y-specific markers in five Colombian Amerind populations. Two of these markers (DYS271, DYS287) are reliable indicators of admixture and detected three non-Amerind chromosomes in our sample. Two other markers (DYS199, M19) are single-nucleotide polymorphisms mostly restricted to Native Americans. The relatedness of chromosomes defined by these two markers was evaluated by constructing haplotypes with seven microsatellite loci (DYS388 to 394). The microsatellite backgrounds found on the two haplogroups defined by marker DYS199 demonstrate the existence of at least two Amerind founder haplotypes, one of them (carrying allele DYS199 T) largely restricted to Native Americans. The estimated age and distribution of these haplogroups places them among the founders of the New World.